Durability of Concrete With Coal Gasification Slag and Coal Gangue Powder - Zhu, Xiaoliang; Guo, Zhaoheng; Yang, Wen; Song, Wenjing (Frontiers in Materials, 2022)
Lack and quality decrease of supplementary cementing materials (SCMs) such as fly ash and granulated blast-furnace slag is increasingly prominent in China. Thus, the use of coal gangue (CG) and coal gasification slag (CGS) as SCMs in concrete attracted more researcher’s attention. This paper investigated the mechanical strength, porosity, durability of CG-and CGS-added concrete. Experimental results showed that the activity of the treated CG and CGS is better than that of ordinary mineral SCMs, indicating that CG and CGS concrete can satisfy the requirements of ordinary construction under reasonable processing technology. Both CG-added and CGS-added concrete illustrated better chloride penetration resistance. The aluminum element contained in CG and CGS causes the C3S hydration generate ettringite which is an erosion product under sulfate erosion, and it will intensify the damage of sulfate erosion. After 125th freeze-thaw cycles, the CGS-added concrete has no obvious failure which indicates that CGS-added concrete has great capacity in the frost resistance. Key words: Durability；Compressive Strength; Coal Gasification Slag；Coal Gangue；Supplementary cementing materials